The East and the West : - Gulick, Sidney Lewis (C.E. Tuttle Co., 1963)
Sidney Lewis Gulick (1860-1945) was an educator, author, and missionary who spent much of his life working to promote greater understanding and friendship between Japanese and American cultures. This compendium draws together 45 years of his studies.